Breeding Zinc Crops for Better Human Health (Springer Nature, 2025)
This open access book discusses Micronutrient Malnutrition (MM) is a major obstacle to the development of human resources in developing nations in Asia and Africa and has been identified as a public health concern. Globally, more than 2 billion people suffer from MM. The most susceptible groups are women and young children under five. The main cause of the persistence of MM prevalence is the inaccessibility, unavailability, or high cost of diets rich in zinc. Typically, staple foods are poor in minerals. An inadequate intake of zinc (Zn) compromises human nutrition and immunological function. Breeding staple crops with enhanced critical nutrients offers a long-term solution for populations dependent on single staples or diets with less diversity. The significance of zinc in human nutrition, high throughput zinc phenotyping techniques, breeding product profile design, new varieties and germplasm that are rich in zinc, and the genetics and genomics of zinc are all covered in this book. For the first time, the publicly available standards (PAS) under the BSI standards for zinc crops were reviewed with an eye toward future global commercial production and commercialization. This edited volume will function as a scientific knowledge base and reference for researchers, graduate students, and other professionals in a comparable field. The goal is to enable biofortification science to help the poor world achieve food and nutrition security.